Peran Penyuluh Pertanian Pada Kelompok Tani Matuari Di Kelurahan Paniki Bawah Kecamatan Mapanget Kota Manado - Sinaga, Miko Tania Nani Vitta; Manginsela, Elsje Pauline; Tambas, Jane Sulinda (Sam Ratulangi University, 2023)
This study aims to describe the role of agricultural extension workers in the Matuari Farmer Group, Paniki Bawah Village, Mapanget District, Manado City. The sampling method in this study is the total sampling method. The data used are primary data and secondary data. The analytical method used in this research is descriptive. The results showed that the role of agricultural extension workers in the Matuari Farmer Group, Paniki Bawah Sub-District, Manado City based on five roles, namely, the role of extension workers as facilitators was categorized as having a moderate role with a score of 40%, the role of extension workers as innovators was categorized as having a less role with a score of 20%, the role of extension workers as educators was categorized as sufficient. played a role with a score of 43%, the role of the extension worker as a motivator was categorized as having a very important role with a score of 80%, and the role of the extension worker as a catalyst was categorized as a very important role with a score of 100%, the role of agricultural extension agents in the Matuari Farmer Group obtained an overall score of 56.5% with a moderate role category.